68.4k views
0 votes
Use Synthetic Division to Factor the following polynomials completely by given factors or roots and Find all the zeros; When you reach quadratic equation, performance regular factoring or Quadratic Formula.


x^(5) -9x^(3) -x^(2) +9;(x-3),(x-1), as factors and -3 as a root

User Regan
by
5.1k points

1 Answer

2 votes

Answer:

The factors are (x - (1 - i√3)/2) , (x - (1 + i√3)/2) , (x - 3) , (x + 3) , (x - 1)

The zeroes are 1 , 3 , -3 , (1 - i√3)/2 , (1 + i√3)/2

Explanation:


(x^(5)+0-9x^(3) -x^(2)+0+9) ÷ (x - 3) =


(x^(4)-9x^(3)-x^(2)+0+9) ÷ (x - 3) =


x^(4)+3x^(3)+(-x^(2)+0+9) ÷ (x - 3) =


x^(4)+3x^(3)-x+(-3x+9) ÷ (x - 3) =


(x^(4)+3x^(3)-x-3)


(x^(4)+3x^(3)+0-x-3) ÷ (x - 1) =

x³ + (4x³ + 0 - x - 3) ÷ (x - 1) =

x³ + 4x² + (4x² - x - 3) ÷ (x - 1) =

x³ + 4x² + 4x + (3x - 3) ÷ (x - 1) =

x³ + 4x² + 4x + 3

∵ -3 is a root ⇒ (x + 3) is a factor

(x³ + 4x² + 4x + 3) ÷ (x + 3) =

x² + (x² + 4x + 3) ÷ (x + 3) =

x² + x + (x + 3) ÷ (x + 3) =

x² + x + 1 ⇒ use the formula to find the factors of this quadratic

∵ a = 1 , b = 1 and c = 1


x=\frac{-1+\sqrt{(1)^(2)-4(1)(1)} }{2(1)}=(-1+√(-3))/(2)=(-1+i√(3))/(2)


x=(-1-i√(3) )/(2)

∴ The factors are (x - (1 - i√3)/2) , (x - (1 + i√3)/2) , (x - 3) , (x + 3) , (x - 1)

The zeroes:

x - 3 = 0 ⇒ x = 3

x + 3 = 0 ⇒ x = -3

x - 1 = 0 ⇒ x = 1

x - (1 - i√3)/2 = 0 ⇒ x = (1 - i√3)/2

x - (1 + i√3)/2 = 0 ⇒ x = (1 + i√3)/2

The zeroes are 1 , 3 , -3 , (1 - i√3)/2 , (1 + i√3)/2

User Rkyr
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.